Experience and management of two cases of fournier’s gangrene in pediatric patients at the Instituto Nacional de Salud del Niño – San Borja, Lima, Peru - Iglesias Guzmán, Martín Humberto (2021)
Fournier’s gangrene is a condition mainly found in adults and it very rarely occurs in children. Multiple predisposing factors have been identified for children, including circumcision, diaper dermatitis, the occurrence of abscesses, anorectal trauma, and immune deficiency. Characteristic signs and symptoms include rapidly progressing edema and hyperemia in the perineal region, accompanied by intense pain and fever. Once Fournier’s gangrene is diagnosed, therapy must be immediately instituted, using wide spectrum intravenous antibiotics and early surgical debridement of devitalized tissues. We present a case report including clinical and epidemiological characteristics of two pediatric patients with Fournier’s gangrene who received medical and surgical therapy at the Instituto Nacional de Salud del Niño in San Borja, Lima, Peru.